GENRE METAMORPHOSIS. PSYCHOGRAM OF SERIAL KILLER (BASED ON THOMAS RAAB NOVEL “SILENCE”) - Megela , I. (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is devoted to the problem of genre hybridization in the novel “Silence. One Killer Chronicle” by modern Austrian writer Thomas Raab. The composition and structure of the novel as a “text in motion”, as becoming of being has been analyzed. The problems of an individual in the context of authoritative power discourse, marginality, Michel Focalut’s nomadism have been elucidated. The final of the novel’s content has been revealed as apotheosis of pain for creativity, feelings sublimation, as birth of an artistic piece and, at the same time, “death of the author”, who exposes discourses, responsible for generating texts which are assigned to him. ___________ References • Vid Ivana, rozdil 1, per. na ukr. I. Ogijenka. Biblija Onlajn https://bibleonline.ru/bible/ukr/43/01/ • BartR. Smert’ avtora. Izbrannye raboty: Semiotika: Pojetika. – M.: Progress, 1994. 615 s. • Brajdotti R. Putem nomadizma. Vvedenie v gendernye issledovanija. Chast’ ІІ. Hrestomatija. SPb, Aletejja, 2001. – S. 136-163 • Deljoz Zh. Logika smysla, per. s fr. Ja. Ja. Svirskogo. – M.: Raritet, 1998. • D’jakov A.V. Mishel’ Fuko: o «smerti cheloveka», o svobode i o «konce filosofii». Vestnik istorii i filosofii KGU 2. Serija «Filosofija» (2008), dostupu: www.jkhora.narod.ru/foucault001.pdf • Il’in I. Postrukturalizm. Dekonstruktivizm. Postmodernizm. – M., 1996, dostup: lib.ru/CULTURE/ILIN/poststrukt.txt_with-big-pictures.html • Kurochkina L.Ja., Pervushkina V. Koncepcija vlasti v Mishelja Fuko. Vestnik Voronezhskogo gosudarstvennogo tehnicheskogo universiteta, Filosofija, 2013. • Lakan Zhak. Instancija bukvy, ili sud’ba razuma posle Frejda, per. s fr. – M.: Russkoe fenomenologicheskoe obshhestvo, izd-vo «Logos», 1997. – 184 s., dostup lib.ru/CULTURE/ILIN/poststrukt.txt_with-big-pictures.html • Liotar, Zhan- Fransua. Sostojanie postmoderna (1979), per. s franc. N. A. Shmatko, «Institut jeksperimental’noj sociologii», M., ALETEJJa, SPb, 1998, dostup lib.ru/CULTURE/LIOTAR/liotar.txt_with-big-pictures.html • Lotman Ju.M. Vnutri mysljashhih mirov. Chelovek-tekst-semiosfera-istorija. – M.: Jazyki russkoj kul’tury, 1996. – 464 s. • Merlo-Ponti. Znaki, per. s fr. I. S. Vdovina. – M., 2001. • Nekrasova I. Celaja vselennaja: K probleme issledovanija pojetiki tishiny 3, dostup soundmuseumspb.ru/gezeta/42-articles/1202-inna-nekrasova • Novikov E. V. Liki nostal’gii.Chelovek 3 (2006): 21-31 • Fuko M. Volja k istine. Po tu storonu znanija, vlasti i seksual’nosti. – M.: Ad Marginem, 1996. – 448 c • Die Presse 18/01/2015 1`6 Salzburger Nachrichten 28.01.2015 • Salzburger Nachrichten 28.01.2015 • Raab. Thomas .Still. Chronik eines Morders-Munchen: Droemer Verlag< 2016. • Westdeutsche Allgemeine 17/04/2015 • Volker Stephan im interview mit Thomas Raab – Bücherkaffee, доступ https://buecherkaffee.de › Interview